Skilled antenatal care services utilisation in sub-Saharan Africa: a pooled analysis of demographic and health surveys from 32 countries - Kwamena Sekyi Dickson; Joshua Okyere; Bright Opoku Ahinkorah; Abdul-Aziz Seidu; Tarif Salihu; Vincent Bediako; Bernard Afriyie Owusu; Eugene Budu; Wonder Agbemavi; Jane Odurowaah Edjah; Eugene Kofuor Maafo Darteh (BMC, 2022)
Abstract Background Each day, an estimated 800 women die from preventable pregnancy and childbirth related complications, where 99% of these avoidable deaths happen in low-and middle-income countries. Skilled attendance during antenatal care (ANC) plays a role in reducing maternal and child mortality. However, the factors that predict the utilisation of skilled ANC services in sub-Saharan Africa (SSA) remains sparsely investigated. Therefore, we examined women's utilisation of skilled ANC services in SSA. Methods The research used pooled data from the most recent Demographic and Health Surveys conducted in 32 countries in SSA between January 1, 2010, and December 31, 2019. Binary logistic regression was used to examine the predictors of skilled ANC services utilisation. The results are presented as crude and adjusted odds ratios (aOR) with 95% confidence interval (CI). Results The prevalence of skilled ANC services utilisation in SSA was 76.0%, with the highest and lowest prevalence in Gambia (99.2%) and Burundi (8.4%), respectively. Lower odds of ANC from skilled providers was found among women aged 45-49 compared to those aged 20-24 (aOR = 0.86, CI = 0.79-0.94); widowed women compared to married women (aOR = 0.84, CI = 0.72-0.99); women who consider getting permission to visit the health facility as a big problem compared to those who consider that as not a big problem (aOR = 0.74, CI = 0.71-0.77); women who consider getting money needed for treatment as not a big problem compared to those who consider that as a big problem (aOR = 0.84, CI = 0.72-0.99); and women who consider distance to the health facility as a big problem compared to those who consider that as not a big problem (aOR = 0.75, CI = 0.72-0.77). Conclusion SSA has relatively high prevalence of skilled ANC services utilisation, however, there are substantial country-level disparities that need to be prioritised. Increasing maternal reproductive age being widowed and far distance to health facility were factors that predicted lower likelihood of skilled ANC services utilisation. There is, therefore, the need to intensify female formal education, invest in community-based healthcare facilities in rural areas and leverage on the media in advocating for skilled ANC services utilisation.